CONSTRAINTS ON MELTING AND MAGMA PRODUCTION IN THE CRUST - Clemens J.D.; Vielzeuf D. (My University, 1987)
Major intrusions of granitic rocks are found in several tectonic settings and, in all cases, crustal melts may contribute to the volumes of granitic magma. High-grade metamorphism and partial melting of the crust take place predominantly under fluid-absent conditions. We present a model for calculating the amounts of melt that may be formed by fluid-absent breakdown of micas and amphiboles in common crustal rock types (pelitic, quartzofeldspathic, intermediate and mafic). Melt proportions depend mainly on the kind of source rock, the pressure at which melting takes place, the temperature and the hydrous mineral (H2O) content of the source. As a consequence of the pressure dependence of water solubility in silicate melts, any given source rock will produce more melt, by a given fluid-absent reaction, at lower pressure. At a given pressure, higher-temperature reactions can produce more melt from a given source rock. Based on a survey of the compositions of common rock types, we show that the amounts of melt can vary from < 10to> 50vol.%. Thus, crustal rocks vary widely in their “fertility” as magma sources, depending on the types and amounts of hydrous phases they contain. In general, muscovite breakdown in pelites will yield only small quantities of melt and lead to migmatite formation. Biotite breakdown in pelites occurs at higher temperature and, because most high-grade pelites (below granulite grade) are biotite-rich, can yield up to about 50 vol.% of granitoid melt. Rocks of intermediate composition and hornblende-rich mafic rocks are potentially highly fertile magma sources also, provided that the high temperatures necessary for biotite and hornblende breakdown are realized. Pyroxene-rich mafic rocks and quartzofeldspathic rocks are much less potentially fertile. Data suggest that mechanisms exist for the efficient segregation of melt and restite in systems with < 30and probably< 20vol.% melt. The pressure-temperature history of a region can greatly influence crustal source fertility through its control over the occurrence of subsolidus dehydration and melting equilibria.